The Influence of Empowerment and Personality Toward Professional Commitment of Indonesian Women’s Navy Corps - Faurna Lusiani Pakpahan; R. Madhakomala; Dedi Purwana (Nusantara Science and Technology Proceedings, 2020)
The personality of the Indonesian Women’s Navy Corps (KOWAL) greatly influences the form of professional commitment that has a good impact on its institution. The objective of this research was to find out and analyze the influence of empowerment and personality of the Indonesian Women’s Navy Corps. The sample of this research was taken by using proportional random sampling. The samples were the Women Navy Corps consisted of 160 respondents from a total of 250 Women Navy Corps. In this research, the researchers used Structural Equation Model in testing, analyzing the data, and model development. The Data were analyzed by using statistical software tools (LISREL 8.8). The results were: 1) Empowerment has a positive direct influence on personality, 2) Empowerment has a positive direct influence on professional commitment, and 3) Personality has a positive direct influence on professional commitment.